Storage stability and in vitro digestion of apigenin encapsulated in Pickering emulsions stabilized by whey protein isolate–chitosan complexes - Ge, Ruihong; Zhu, Haihua; Zhong, Jian; Wang, Hui; Tao, Ningping (Frontiers in Nutrition, 2022)
Few studies have investigated the encapsulation of apigenin in solid particle-stabilized emulsions. In this work, Pickering emulsions containing apigenin and stabilized by whey protein isolate-chitosan (WPI-CS) complexes were created to enhance the bioavailability of apigenin. Different lipids including medium-chain triglycerides (MCTs), ethyl oleate (EO), and corn oil (CO) were selected to fabricate lipid-based delivery systems. The microstructure of the Pickering emulsions, as revealed by optical and cryo-scanning electron microscopies, showed that the oil droplets were dispersed evenly and trapped by a three-dimensional network formed by the WPI-CS complexes, which was further confirmed by rheology properties. After thirty days of storage, Pickering emulsions with MCTs achieved the highest apigenin retention rate, exhibiting 95.05 ± 1.45% retention when stored under 4 °C. In vitro gastrointestinal tract experiments indicated that the lipid types of the emulsions also affected the lipid digestion and release rate of apigenin. Pickering emulsions with MCTs achieved a higher bioaccessibility compared to that of the other two emulsions (p ˂ 0.01). These results indicate that the delivery system of Pickering emulsions with MCTs stabilized by WPI-CS complexes offers good storage stability and improved bioaccessibility of apigenin.